2019
DOI: 10.3892/etm.2019.7355
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of phenylethanoid glycosides, Torenoside�B and Savatiside A, in Alzheimer's disease

Abstract: The current study assessed the efficacy of two phenylethanoid glycosides (PhGs), Torenoside B (TB) and Savatiside A (SA), in the treatment of Alzheimer's disease (AD). The effects of TB and SA compounds were first assessed following amyloid beta (Aβ) 25-35 induction in SH-SY5Y cells at a range of concentrations. Their effects on cell viability and reactive oxygen species (ROS) were determined by performing MTT and dichlorofluorescin diacetate assays, respectively. The concentration of intracellular Ca 2+ was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…e pharmacological actions of C-glycosyl flavones may have antioxidative, antiradiation, cardiovascular protective, and hypoglycemic effects [5]. Phenylethanoid glycosides exhibit a wide range of curative bioactivities, such as antibacterial, anti-inflammatory, antiviral, and neuroprotective, as well as other effects [6]. Previous studies in our laboratory showed that C. flabellata increased rats' urine volume and alleviated symptoms of Alzheimer's disease (AD) in a rat model of AD.…”
Section: Introductionmentioning
confidence: 99%
“…e pharmacological actions of C-glycosyl flavones may have antioxidative, antiradiation, cardiovascular protective, and hypoglycemic effects [5]. Phenylethanoid glycosides exhibit a wide range of curative bioactivities, such as antibacterial, anti-inflammatory, antiviral, and neuroprotective, as well as other effects [6]. Previous studies in our laboratory showed that C. flabellata increased rats' urine volume and alleviated symptoms of Alzheimer's disease (AD) in a rat model of AD.…”
Section: Introductionmentioning
confidence: 99%
“…As previously described (Jiang and Tu, 2009), TGs contain lots of bioactive compounds, for example echinacoside, tubuloside A, acteoside, isoacteoside and 2'-acetylacteoside, and some of them showed neuroprotective functions after cerebral I/R injury (Peng et al, 2016). Echinacoside has lots of pharmacological effects, such as antioxidation, anti-senescence, neuroprotection, anti-inflammation, promotion of cicatrization, hepatoprotection, promotion of bone formation and anti-tumor activities (Yu et al, 2016;Li et al, 2018;Ji et al, 2019;Xu et al, 2019). Recently, echinacoside has been identified as a potent antioxidant in the central nervous system (Lu et al, 2016).…”
Section: Discussionmentioning
confidence: 85%
“…The human neuroblastoma cell lines SH-SY5Y and BE(2)-M17 are two of the best-characterised cell lines for studies into human neurological disease, such as Alzheimer’s and Parkinson’s diseases (3035), and neurovirology (3946, 49, 52). Previous studies have confirmed their suitability as in vitro models of human neurons due to their expression of human neuron-specific markers, and the fact that their neuron-like phenotypes can be further improved through the use of chemical differentiation agents, such as RA and staurosporine (3638, 43).…”
Section: Discussionmentioning
confidence: 99%
“…Human neuroblastoma cell lines, including SH-SY5Y and BE(2)-M17 cells, are commonly used for in vitro analysis in neuroscience research into conditions such as Alzheimer’s and Parkinson’s disease, and are widely considered to be appropriate in vitro models for human neurons given their expression of neuron-specific factors and markers (3035). The quality of the neuron-like phenotypes (both morphological and biochemical) of these cell lines can be increased through the use of chemical differentiation, often involving drugs such as trans -retinoic acid (RA) or staurosporine (3638).…”
Section: Introductionmentioning
confidence: 99%